Voh Winkel′s Syndrome With Unusual Features - Ravikumar B C; Balachandran C; Sabitha L (Wolters Kluwer Medknow Publications, 1997)
Voh winkelâ€s syndrome is a rare disease. Here a case of Voh winkelâ€s syndrome is described with associated icthyosis vulgaris like dermatoses, ectropion and nail changes.